The content and structure of phenomenon “Сulture of professional communication” in the context of teacher-engineer’s professional activity - Kochyna, V. (Problems of Engineer-Pedagogical Education, 2018)
This article is analysed the investigation condition and problem of culture professional communication formation for engineer-pedagogical specialty students. A concept "the culture of professional communication of future teacher-engineers of a transport industry" is defined as an integral formation personality that provides a process of information exchange and achievement of optimal cooperation of its participants. It is characterized the totality of loop invariant and variation knowledge and abilities of professional communication realization, where the variation is determined by these specialists types of professional activity and personality qualities complex that provide the professional communication process. The content and structure of phenomenon «the professional communication culture» are analysed. It was proposed with different scientists and it gives the chance to dedicate its components: motivational- valued, cognitive, activity approach, personality. The every component characteristic of culture professional communication of future teacher-engineers of transport industry is given. The motivational- valued component shows the professional communication orientation, motivation and interest foe its realization, an interest in professional cooperation, the determination of communication culture as personality value; the cognitive component comprises loop invariant knowledge of process realization for the professional communication and variant knowledge for its actions by the types of teacher-engineer professional activity; the activity approach is characterized the complex of loop invariant skills for the realization of professional communication process and variation skills for its realization by the types of professional activity for teacher-engineers of transport industry; the personality represents the humanist attitude of teacher to the interlocutor, tolerance, empathy, reflection, capacity for selfcontrol.